Surveying the scene: A review of how landscapes are valued - Andrés Pazmiño; Edward A. Morgan; Aysin Dedekorkut-Howes; Michael Howes (Landscape and Urban Planning, 2026)

Carbon stock and flux predictions in second-growth Sitka-spruce and western hemlock dominated stands of Southeast Alaska - Dryw A. Jones; David V. D’Amore; Kellen N. Nelson; Frances Biles; Michael C. Howe (Forest Ecology and Management, 2026)

Warming Temperatures to Expand Spruce Beetle Outbreak Distribution in Northern but Not Southern Picea Forests of Western North America - Michael C. Howe; Karen Hutten; Jessie Moan; Kellen N. Nelson (Journal of Biogeography, 2026)
Aim The biogeography and distribution of irruptive forest insect herbivores are driven by population level responses to host availability, temperature, and precipitation. Because the irruptive dynamics of tree‐killing insects such as spruce beetle are regulated by climate, it is imperative to quantify biogeographic drivers and limiters to develop informed predictions and forecasts of future outbreaks. Here, we: (1) identify subcontinental drivers of spruce beetle outbreak distributions, (2) compare drivers and limiters of outbreaks across regions, and (3) develop geospatial hindcasts and forecasts to evaluate the potential for shifts in outbreak activity through time. Location Western North American spruce forests spanning 33 to 68 degrees latitude. Taxon Spruce beetle ( Dendroctonus rufipennis ) and spruce trees ( Picea spp.) Methods We compiled aerial surveys of spruce beetle‐caused tree mortality from 1962 to 2023, forest inventory, and downscaled climate data to develop ensemble machine learning models to investigate patterns of recorded outbreaks and predict the historical and projected distributions of spruce beetle outbreaks. Results The distribution of spruce beetle outbreaks are best explained by minimum winter temperature, precipitation as snow, and mean growing season temperatures across western North American. Limiters of outbreaks varied regionally. Host occupancy limited the southern distribution, abundant moisture and diffuse host availability in mixed species forests constrained the western coastal distribution, and minimum winter temperature constrained the northern distribution. Hindcasts and forecasts indicate that the outbreak distribution has expanded in all regions since 1900 and will continue to expand poleward due to projected warming across the boreal. Conclusions Understanding how the distributions of forest insect outbreaks respond to fluctuations in climate will dictate the location and severity of outbreaks over the next century. Large‐scale irruptions of spruce beetle in forests with historically limited activity will lead to substantial impacts on spruce‐dominated landscapes and unknown ramifications for forest processes or long‐term disturbance regimes.

Autophagy-dependent cell death and immune responses induced by heteroleptic copper(II), manganese(II), and silver(I) complexes containing dicarboxylate and 1,10-phenanthroline ligands: novel insights from in vitro and in vivo models - Ella O’Sullivan; Denis O’Shea; Michael Devereux; Kevin Kavanagh; Orla Howe (BioMetals, 2026)

Determinants of pesticide exposure among girls in rural Costa Rica: A silicone wristband study - Mecca E. Howe; Yaw Edu Essandoh; Kevin Romanak; Chunjie Xia; Genesis Brenes Alvarado; Greivin Salazar Bravo; Michael Wasserman; Andrea S. Wiley; Marta Venier (Environmental Pollution, 2025)

Apoptotic cell death induced by copper (II), manganese (II) and silver (I) complexes containing bridging dicarboxylate and 1,10-phenanthroline ligands: one of the multi-modes of anticancer activity? - Ella O’Sullivan; Denis O’Shea; Michael Devereux; Orla Howe (BioMetals, 2025)
Cu(II), Mn(II) and Ag(I) complexes incorporating bridging dicarboxylate and 1,10-phenanthroline ligands have exhibited anti-cancer potential with significant in vitro and in vivo cytotoxic efficacies. Our study focuses on regulated cell death process of apoptosis as a mode of action of the anti-cancer activity by the complexes. Cytotoxicity screening of the complexes demonstrated all the metal-dicarboxylate-phenanthroline complexes exhibit superior activity compared to their non-phenanthroline containing precursors, in addition to cisplatin. The Cu(II) and Mn(II) complexes were shown to induce reactive oxygen species (ROS) but this was not observed for the Ag(I) analogues. Furthermore, apoptosis was found to be induced by all the metal-phenanthroline complexes to varying degrees contingent on the type of metal centre in the complex. Apoptotic gene expression analysis established the predominant activation of the intrinsic apoptotic pathway, with co-stimulation of the extrinsic pathway observed in some cases. The mechanistic data provided within this study highlights the multi-modal activity of the metal-phenanthroline complexes contingent on the type of metal present, warranting continued investigation of their biological modes of action beyond apoptosis induction.

Forest restoration can bolster salmon population persistence under climate change - Michele S. Buonanduci; Eric R. Buhle; Michael J. Case; Emily R. Howe; James C. Robertson; Nicholas VanBuskirk; Ailene K. Ettinger (Biological Conservation, 2025)

A shrinking envelope? Climate warming across the Pacific coastal temperate rainforest and its projected impact on a native defoliator - Michael Howe; Elizabeth E Graham; Kellen N Nelson (Climatic Change, 2025)

Quantification of heritable variation in multiple lodgepole pine chemical and physical traits that contribute to defense against mountain pine beetle (Dendroctonus ponderosae) - Michael Howe; Alvin Yanchuk; Kimberly F. Wallin; Kenneth F. Raffa (Forest Ecology and Management, 2024)

Current and future directions in research on community gardens - Jesse Raneng; Michael Howes; Catherine Marina Pickering (Urban Forestry & Urban Greening, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Antibacterial activity of metal–phenanthroline complexes against multidrug-resistant Irish clinical isolates: a whole genome sequencing approach - Megan O’Shaughnessy; Jasmine Hurley; Shane C. Dillon; Celine Herra; Pauraic McCarron; Malachy McCann; Michael Devereux; Orla Howe (JBIC Journal of Biological Inorganic Chemistry, 2022)

Development of a High-Dose Infant Air-Jet Dry Powder Inhaler (DPI) with Passive Cyclic Loading of the Formulation - Connor Howe; Mohammad A. M. Momin; Ghali Aladwani; Michael Hindle; P. Worth Longest (Pharmaceutical Research, 2022)

The quest for ghost gear in the German Baltic Sea: A team effort between WWF, divers, fisherfolk, and public authorities - Andrea Stolte; Gabriele Dederer; Jochen Lamp; Crayton Fenn; Mareen Lee; Wolfgang Frank; Christian Howe; Michael Günther; Heike Vesper; Stefanie Werner (Frontiers in Marine Science, 2022)
In this pilot project, World Wild Fund for Nature (WWF) Germany works together with regional divers, fisherfolk and public authorities to reduce the impact of lost fishing gear in the Baltic Sea. If not removed, ghost gear poses a threat to the marine environment and wildlife including seabirds, seals, harbour porpoises and fish. Over decades to centuries, lost fishing nets and ropes shed microplastic fibres into the marine environment. Removing this hazard reduces both the risk of entanglement as well as the contamination of the marine foodweb through ingestion of microplastics and associated chemicals. Identifying lost fishing gear in the marine environment poses one of the largest challenges impeding mitigation through gear retrieval operations. Lost gear can be drifting on the surface, in the water column, or can be sunken to the seafloor as a result of material composition, fouling, and entanglement. In the Baltic Sea, ghost gear is located on the seafloor and not visible during visual surface surveys from vessels. Identifying an efficient search methodology was therefore a key aspect of WWF’s ghost gear project. After trials with different search and retrieval methodologies, WWF Germany found sonar search technology to be the most efficient technique to locate lost gear on the seafloor. Sound waves avoid the limitations faced by divers or visual cameras in low-visibility environments, and a substantially larger area can be covered. In contrast to diving teams focussing on wreck retrievals, the many nets lost on the seafloor remain unnoticed by divers under most circumstances. A combination of sonar search providing exact GPS positions of suspect ghost gear, diver verification through the WWF Ghostdiver App, point-on retrievals with fishing vessels, and manual sorting for waste management provides an efficient methodology for long-term political implementation of regular lost gear retrieval campaigns.

Characterizing the Effects of Nasal Prong Interfaces on Aerosol Deposition in a Preterm Infant Nasal Model - Karl Bass; Mohammad A. M. Momin; Connor Howe; Ghali Aladwani; Sarah Strickler; Arun V. Kolanjiyil; Michael Hindle; Robert M. DiBlasi; Worth Longest (AAPS PharmSciTech, 2022)
The objective of this study was to characterize the effects of multiple nasal prong interface configurations on nasal depositional loss of pharmaceutical aerosols in a preterm infant nose-throat (NT) airway model. Benchmark in vitro experiments were performed in which a spray-dried powder formulation was delivered to a new preterm NT model with a positive-pressure infant air-jet dry powder inhaler using single- and dual-prong interfaces. These results were used to develop and validate a computational fluid dynamics (CFD) model of aerosol transport and deposition in the NT geometry. The validated CFD model was then used to explore the NT depositional characteristic of multiple prong types and configurations. The CFD model highlighted a turbulent jet effect emanating from the prong(s). Analysis of NT aerosol deposition efficiency curves for a characteristic particle size and delivery flowrate (3 µm and 1.4 L/min (LPM)) revealed little difference in NT aerosol deposition fraction (DF) across the prong insertion depths of 2–5 mm (DF = 16–24%) with the exception of a single prong with 5-mm insertion (DF = 36%). Dual prongs provided a modest reduction in deposition vs. a single aerosol delivery prong at the same flow for insertion depths Graphical Abstract

Exploring the Use of Seabirds as a Dynamic Ocean Management Tool to Mitigate Anthropogenic Risk to Large Whales - Tammy L. Silva; Kevin D. Powers; Jooke Robbins; Regina Asmutis-Silvia; Timothy V. N. Cole; Alex N. Hill; Laura J. Howes; Charles A. Mayo; Dianna Schulte; Michael A. Thompson; Linda J. Welch; Alexandre N. Zerbini; et al. (Frontiers in Marine Science, 2022)
Vessel strike and entanglement in fishing gear are global threats to large whales. United States management actions to reduce human-induced serious injury and mortality to large whales have been inadequate, partially due to static, spatial protection schemes that fail to adjust to distribution shifts of highly mobile animals. Whale conservation would benefit from dynamic ocean management, but few tools exist to inform dynamic approaches. Seabirds are often found in association with whales and can be tagged at lower cost and in higher numbers than whales. We explored the use of satellite-tagged seabirds (great shearwaters) as dynamic ocean management tools for near real-time identification of habitats where humpback and North Atlantic right whales aggregate, potentially increasing anthropogenic risk. We identified shearwater habitat use areas in the Gulf of Maine with 50% kernel density utilization distributions at yearly, monthly, and weekly scales using satellite-telemetry data from 2013-2018. We quantified overlap using whale sightings and whale satellite telemetry data at two spatial scales: Stellwagen Bank National Marine Sanctuary and the Gulf of Maine. Within the sanctuary, shearwaters overlapped with >50% of humpback sightings in 4 of 6 (67%) years, 15 of 23 (65%) months, and 50 of 89 (56%) of weeks. At the Gulf of Maine scale, shearwater use areas overlapped >50% of humpback sightings in 5 of 6 years (83%) and 16 of 22 (73%) months, and encompassed humpback 50% utilization distributions (based on satellite telemetry) in 2 of 3 (66%) years and 7/12 (58%) months analyzed. Overlap between shearwaters and right whales was much lower, with >50% overlap in only 1 of 6 (17%) years and 3 of 23 (13%) months. These initial results demonstrate that satellite-tagged shearwaters can be indicators of humpback whale habitat use in both space and time. With further study, tagged shearwaters may provide near-real time information necessary to operationalize dynamic management to mitigate human impacts on humpback whales.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The acute effects of cannabidiol on emotional processing and anxiety: a neurocognitive imaging study - Michael A. P. Bloomfield; Yumeya Yamamori; Chandni Hindocha; Augustus P. M. Jones; Jocelyn L. L. Yim; Hannah R. Walker; Ben Statton; Matthew B. Wall; Rachel H. Lees; Oliver D. Howes; Valerie H. Curran; Jonathan P. Roiser; et al. (Psychopharmacology, 2022)
Rationale There is growing interest in the therapeutic potential of cannabidiol (CBD) across a range of psychiatric disorders. CBD has been found to reduce anxiety during experimentally induced stress in anxious individuals and healthy controls. However, the mechanisms underlying the putative anxiolytic effects of CBD are unknown. Objectives We sought to investigate the behavioural and neural effects of a single dose of CBD vs. placebo on a range of emotion-related measures to test cognitive-mechanistic models of its effects on anxiety. Methods We conducted a randomised, double-blind, placebo-controlled, crossover, acute oral challenge of 600 mg of CBD in 24 healthy participants on emotional processing, with neuroimaging (viewing emotional faces during functional magnetic resonance imaging) and cognitive (emotional appraisal) measures as well as subjective response to experimentally induced anxiety. Results CBD did not produce effects on brain responses to emotional faces and cognitive measures of emotional processing, or modulate experimentally induced anxiety, relative to placebo. Conclusions Given the rising popularity of CBD for its putative medical benefits, these findings question whether further research is warranted to investigate the clinical potential of CBD for the treatment of anxiety disorders.

Numbers matter: how irruptive bark beetles initiate transition to self-sustaining behavior during landscape-altering outbreaks - Michael Howe; Kenneth F. Raffa; Brian H. Aukema; Claudio Gratton; Allan L. Carroll (Oecologia, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Climate‐induced outbreaks in high‐elevation pines are driven primarily by immigration of bark beetles from historical hosts - Michael Howe; Allan Carroll; Claudio Gratton; Kenneth F. Raffa (Global Change Biology, 2021)
Warming temperatures are allowing native insect herbivores to expand into regions that previously exceeded their thermal tolerance, encounter new host species, and pose significant threats to native communities. However, the dynamics of these expansions remain poorly understood, particularly in the extent to which outbreaks remain reliant on emigration from historical hosts or are driven by local reproduction within novel hosts in the expanded range. We tested these non‐mutually exclusive hypotheses using spatially explicit data on mountain pine beetle ( Dendroctonus ponderosae ), which historically undergoes intermittent outbreaks in low‐elevation lodgepole pine ( Pinus contorta ), but is now causing severe mortality in a high‐elevation endangered species, whitebark pine ( Pinus albicaulis ). We compiled data from 2000 to 2019 across British Columbia, Canada, at 1‐km 2 resolution, and analyzed spatiotemporal patterns of beetle infestations, lodgepole pine distributions, expansion into habitats dominated by whitebark pine, and the likelihood of future outbreaks in all pine communities under simulated conditions. Overall, we found strong support for the hypothesis of emigration from the historical host species continuing to be a major driver of outbreaks in the more recently accessed host. First, beetle population pressure was consistently the best predictor of infestation severity in both lodgepole and whitebark pine, and appeared to be mostly unidirectional from lodgepole to whitebark pine. Second, infestations in lodgepole pine were of a longer duration than those in whitebark pine, which appeared too brief to sustain transitions from endemic to eruptive dynamics. Furthermore, resource depletion appears to drive emigration from lodgepole pine, whereas in whitebark pine drought appears to favor establishment of immigrants although bioclimatic factors and stand structure preclude self‐sustaining outbreaks. Finally, we project that most pine in British Columbia will be at risk in the event of a new major outbreak. We describe implications for conserving and protecting whitebark pine and to other climate‐driven range expansions.

Advancement of the Infant Air-Jet Dry Powder Inhaler (DPI): Evaluation of Different Positive-Pressure Air Sources and Flow Rates - Connor Howe; Mohammad A.M. Momin; Dale R. Farkas; Serena Bonasera; Michael Hindle; P. Worth Longest (Pharmaceutical Research, 2021)

Corrigendum: On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)

On a Reef Far, Far Away: Anthropogenic Impacts Following Extreme Storms Affect Sponge Health and Bacterial Communities - Amanda Shore; Jordan A. Sims; Michael Grimes; Lauren I. Howe-Kerr; Carsten G. B. Grupstra; Shawn M. Doyle; Lauren Stadler; Jason B. Sylvan; Kathryn E. F. Shamberger; Sarah W. Davies; Lory Z. Santiago-Vázquez; Adrienne M. S. Correa (Frontiers in Marine Science, 2021)
Terrestrial runoff can negatively impact marine ecosystems through stressors including excess nutrients, freshwater, sediments, and contaminants. Severe storms, which are increasing with global climate change, generate massive inputs of runoff over short timescales (hours to days); such runoff impacted offshore reefs in the northwest Gulf of Mexico (NW GoM) following severe storms in 2016 and 2017. Several weeks after coastal flooding from these events, NW GoM reef corals, sponges, and other benthic invertebrates ∼185 km offshore experienced mortality (2016 only) and/or sub-lethal stress (both years). To assess the impact of storm-derived runoff on reef filter feeders, we characterized the bacterial communities of two sponges, Agelas clathrodes and Xestospongia muta , from offshore reefs during periods of sub-lethal stress and no stress over a three-year period (2016—2018). Sponge-associated and seawater-associated bacterial communities were altered during both flood years. Additionally, we found evidence of wastewater contamination (based on 16S rRNA gene libraries and quantitative PCR) in offshore sponge samples, but not in seawater samples, following these flood years. Signs of wastewater contamination were absent during the no-flood year. We show that flood events from severe storms have the capacity to reach offshore reef ecosystems and impact resident benthic organisms. Such impacts are most readily detected if baseline data on organismal physiology and associated microbiome composition are available. This highlights the need for molecular and microbial time series of benthic organisms in near- and offshore reef ecosystems, and the continued mitigation of stormwater runoff and climate change impacts.

Search for top‐down and bottom‐up drivers of latitudinal trends in insect herbivory in oak trees in Europe - Elena Valdés‐Correcher; Xoaquín Moreira; Laurent Augusto; Luc Barbaro; Christophe Bouget; Olivier Bouriaud; Manuela Branco; Giada Centenaro; György Csóka; Thomas Damestoy; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Global Ecology and Biogeography, 2021)
Aim The strength of species interactions is traditionally expected to increase toward the Equator. However, recent studies have reported opposite or inconsistent latitudinal trends in the bottom‐up (plant quality) and top‐down (natural enemies) forces driving herbivory. In addition, these forces have rarely been studied together thus limiting previous attempts to understand the effect of large‐scale climatic gradients on herbivory. Location Europe. Time period 2018–2019. Major taxa studied Quercus robur . Methods We simultaneously tested for latitudinal variation in plant–herbivore–natural enemy interactions. We further investigated the underlying climatic factors associated with variation in herbivory, leaf chemistry and attack rates in Quercus robur across its complete latitudinal range in Europe. We quantified insect leaf damage and the incidence of specialist herbivores as well as leaf chemistry and bird attack rates on dummy caterpillars on 261 oak trees. Results Climatic factors rather than latitude per se were the best predictors of the large‐scale (geographical) variation in the incidence of gall‐inducers and leaf‐miners as well as in leaf nutritional content. However, leaf damage, plant chemical defences (leaf phenolics) and bird attack rates were not influenced by climatic factors or latitude. The incidence of leaf‐miners increased with increasing concentrations of hydrolysable tannins, whereas the incidence of gall‐inducers increased with increasing leaf soluble sugar concentration and decreased with increasing leaf C : N ratios and lignins. However, leaf traits and bird attack rates did not vary with leaf damage. Main conclusions These findings help to refine our understanding of the bottom‐up and top‐down mechanisms driving geographical variation in plant–herbivore interactions, and indicate the need for further examination of the drivers of herbivory on trees.

Publisher Correction to: Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

Integrating adverse effect analysis into environmental risk assessment for exotic generalist arthropod biological control agents: a three-tiered framework - Débora P. Paula; David A. Andow; Barbara I. P. Barratt; Robert S. Pfannenstiel; Philippa J. Gerard; Jacqui H. Todd; Tania Zaviezo; Maria G. Luna; Claudia V. Cédola; Antoon J. M. Loomans; Andy G. Howe; Michael D. Day; et al. (BioControl, 2021)

UBC-Nepal expedition: dynamic cerebral autoregulation is attenuated in lowlanders upon ascent to 5050 m - Michael M. Tymko; Alexander B. Hansen; Joshua C. Tremblay; Alexander Patrician; Ryan L. Hoiland; Connor A. Howe; Matthew G. Rieger; Philip N. Ainslie (European Journal of Applied Physiology, 2020)

Transforming growth factor-β promotes basement membrane fibrosis, alters perivascular cerebrospinal fluid distribution, and worsens neurological recovery in the aged brain after stroke - Matthew D. Howe; J. Weldon Furr; Yashasvee Munshi; Meaghan A. Roy-O’Reilly; Michael E. Maniskas; Edward C. Koellhoffer; John d’Aigle; Lauren H. Sansing; Louise D. McCullough; Akihiko Urayama (GeroScience, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Photogrammetry of blue whales with an unmanned hexacopter - John W. Durban; Michael J. Moore; Gustavo Chiang; Leigh S. Hickmott; Alessandro Bocconcelli; Gloria Howes; Paulina A. Bahamonde; Wayne L. Perryman; Donald J. LeRoi (Marine Mammal Science, 2016)

Influences of Natural and Anthropogenic Factors and Tidal Restoration on Terrestrial Arthropod Assemblages in West Coast North American Estuarine Wetlands - Aaron T. David; Pascale A. L. Goertler; Stuart H. Munsch; Brittany R. Jones; Charles A. Simenstad; Jason D. Toft; Jeffery R. Cordell; Emily R. Howe; Ayesha Gray; Michael P. Hannam; William Matsubu; Erin E. Morgan (Estuaries and Coasts, 2016)

Barriers to Effective Genome Editing of Haematopoietic Stem Cells - Steven J. Howe; Michael D. Milsom (Current Stem Cell Reports, 2016)

How functional traits, herbivory, and genetic diversity interact in Echinacea : implications for fragmented populations - Pamela M. Kittelson; Stuart Wagenius; Reina Nielsen; Sanjive Qazi; Michael Howe; Gretel Kiefer; Ruth G. Shaw (Ecology, 2015)
Habitat fragmentation produces small, spatially isolated populations that promote inbreeding. Remnant populations often contain inbred and outbred individuals, but it is unclear how inbreeding relative to outbreeding affects the expression of functional traits and biotic interactions such as herbivory. We measured a suite of 12 functional traits and herbivore damage on three genotypic cross types in the prairie forb, Echinacea angustifolia : inbred, and outbred crosses resulting from matings within and between remnant populations. Inbreeding significantly affected the expression of all 12 functional traits that influence resource capture. Inbred individuals had consistently lower photosynthetic rates, water use efficiencies, specific leaf areas, and had higher trichome numbers, percent C, and percent N than outbred individuals. However, herbivore damage did not differ significantly among the cross types and was not correlated with other leaf functional traits. Leaf architecture and low physiological rates of the inbred compared to outbred individuals imply poorer capture or use of resources. Inbred plants also had lower survival and fitness relative to outbred plants. Our results show that inbreeding, a phenomenon predicted and observed to occur in fragmented populations, influences key functional traits such as plant structure, physiology and elemental composition. Because of their likely role in fitness of individuals and ecological dynamics plant functional traits can serve as a bridge between evolution and community or ecosystem ecology.

Using SWAT for sub-field identification of phosphorus critical source areas in a saturation excess runoff region - Michael F. Winchell; Solomon Folle; Donald Meals; Julie Moore; Raghavan Srinivasan; Eric A. Howe (Hydrological Sciences Journal, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

High-density miniaturized seed orchards of Douglas-fir - Scott E. Kolpak; Jim Smith; Michael J. Albrecht; Jeff DeBell; Sara Lipow; Marilyn L. Cherry; Glenn T. Howe (New Forests, 2015)

The link between dopamine function and apathy in cannabis users: an [18F]-DOPA PET imaging study - Michael A. P. Bloomfield; Celia J. A. Morgan; Shitij Kapur; H. Valerie Curran; Oliver D. Howes (Psychopharmacology, 2014)

The Eltanin asteroid impact: possible South Pacific palaeomegatsunami footprint and potential implications for the Pliocene–Pleistocene transition - James Goff; Catherine Chagué‐Goff; Michael Archer; Dale Dominey‐Howes; Chris Turney (Journal of Quaternary Science, 2012)
Large asteroid impacts are rare, and those into the deep ocean are rarer still. The Eltanin asteroid impact around 2.51 ± 0.07 Ma occurred at a time of great climatic and geological change associated with the Pliocene–Pleistocene boundary. Numerical models of the event indicate that a megatsunami was generated, although there is debate concerning its magnitude and the region‐wide extent of its influence. We summarise the existing evidence for possible Eltanin megatsunami deposits in Antarctica, Chile and New Zealand, while also examining other potential sites from several locations, mainly around the South Pacific region. In reviewing these data we note that these events were unfolding at the same time as those associated with the Pliocene–Pleistocene boundary and, as such, most of the geological evidence from that time has a climatic interpretation. The potential climatic and geological ramifications of the Eltanin asteroid impact, however, have failed to be considered by most researchers studying this time period. Although we are not advocating that all geological activity at that time is connected with the Eltanin asteroid impact, it raises interesting questions about the role potentially played by such catastrophic events in contributing to or even triggering epochal transitions. Copyright © 2012 John Wiley & Sons, Ltd.

Genetic diversity and phylogeography of broomcorn millet ( Panicum miliaceum L.) across Eurasia - HARRIET V. HUNT; MICHAEL G. CAMPANA; MATTHEW C. LAWES; YONG‐JIN PARK; MIM A. BOWER; CHRISTOPHER J. HOWE; MARTIN K. JONES (Molecular Ecology, 2011)

Mass-Spring Model for Simulation of Heart Valve Tissue Mechanical Behavior - Peter E. Hammer; Michael S. Sacks; Pedro J. del Nido; Robert D. Howe (Annals of Biomedical Engineering, 2011)

Structural and kinetic studies of imidazole binding to two members of the cytochrome c 6 family reveal an important role for a conserved heme pocket residue - Badri S. Rajagopal; Michael T. Wilson; Derek S. Bendall; Christopher J. Howe; Jonathan A. R. Worrall (JBIC Journal of Biological Inorganic Chemistry, 2011)

A national framework for cancer surveillance in the United States - Phyllis A. Wingo; Holly L. Howe; Michael J. Thun; Rachel Ballard-Barbash; Elizabeth Ward; Martin L. Brown; JoAnne Sylvester; Gilbert H. Friedell; Linda Alley; Julia H. Rowland; Brenda K. Edwards (Cancer Causes & Control, 2005)

The research potential of tissue from a cadaveric donor - Christopher Womack; Neil M. Gray; Lesley J. Howes; Michael D. Harris (Cell and Tissue Banking, 2002)